Differential metabolic rearrangements after cold storage are correlated with chilling injury resistance of peach fruits - Bustamante, Claudia Anabel (2016)
Fil: Fil: Bustamante, Claudia Anabel. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Centro de Estudios Fotosintéticos y Bioquímicos (CEFOBI-CONICET); Argentina.